Sosialiasi Mengenai Masa Tua yang Sehat dengan Mengenal Manfaat Teh Bunga Telang untuk Tubuh pada Masyarakat Desa Sojomerto - Elsa Sabina Putri Latifah; Nuralisah Meiliani Putri; Millatul Azizah; Mita Agustia; Fatma Nur Himatul Aliyah; Nahnu Robid Jiwandono (Lembaga Pengembangan Kinerja Dosen, 2024)
The decline in physical and mental abilities is an inevitable sign of the aging phase. Maintaining health in old age involves not only physical activity and a balanced diet but also utilizing natural ingredients that can support overall body health. One such natural ingredient with significant potential to support health in old age is butterfly pea flower (Clitoria ternatea), known for its numerous health benefits, including stress reduction and cognitive function support. To raise awareness of the importance of preparing for healthy aging, the KKN MIT-18 Posko 57 Sojomerto Village team organized a seminar and workshop titled